ANALISIS PENERAPAN MANAJEMEN HUBUNGAN PELANGGAN PADA UMKM ALMIRA’S CAKE DIKOTA BATAM - Hasan, Golan; Indah, Indah; Sherlen, Sherlen; Tan, Selina; Ardianata, Kristi; Frenky, Frenky; Rooney, Rooney; Derry, Derry (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in driving national economic growth, including in Batam City, which is showing rapid development in the food and beverage sector. Almira’s Cake, as one of the local MSMEs engaged in home cake production, shows great potential in attracting and retaining consumers. However, relationships with customers are still built conventionally without a structured Customer Relationship Management (CRM) system. This research aims to analyze the extent of CRM implementation at Almira’s Cake and evaluate opportunities for developing a more effective CRM strategy. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observations, and literature studies. The results of this study are expected to provide a deeper understanding of the importance of CRM in increasing customer loyalty and competitiveness of MSMEs in the midst of a competitive market.